Late Quaternary hydrographic evolution in Thessaly (Central Greece): The crucial role of the Piniada Valley. (20th October 2022) - Caputo, R.; Helly, B.; Rapti, D.; Valkaniotis, S.
Abstract: The present-day hydrographic network of the Pinios River, Greece, clearly shows some major morphological and hydrographic anomalies documenting its complex evolution. A critical analysis and re-interpretation of geological and historical/modern topographic data clearly indicate an original subdivision of Thessaly into two separate endorheic hydrographic networks, Karditsa and Larissa realms. At different epochs, these two basins were partially covered by lake waters and/or marsh areas up to late Antiquity and locally/temporarily even in recent historical periods. The Piniada Valley is in between the two major (present-day) alluvial plains existing in Thessaly. The pre-infilling morphology of the valley bottom has been recently reconstructed suggesting it likely represented the lower reach of the Titarissios River draining into the Karditsa basin. These environmental-depositional conditions persisted up to Late Pleistocene when tectonic activity along the Tyrnavos and Larissa faults diverted the lower reach of this river into the Larissa area causing the abandonment of the Piniada Valley. Depending on the water discharge along the western Thessalian rivers and the consequent water level fluctuations of the Karditsa Lake, together with the gradual infilling of the basin, the Piniada Valley and especially its western sector was then largely affected by lacustrine-to-marshy conditions. This was also due to the lacking of a permanent hydrographic network draining the area. Indeed, the present-day Pinios River could form only after the prograding 'western' rivers completely infilled the Karditsa basin by generating a hydrographic network in the plain. Only in the latest stage of this process, the Piniada Valley was characterized by fluvial aggradation, causing the alluvial plain to expand eastwards finally reaching the altimetric threshold of the Kalamaki Gorge. This last phenomenon definitely established a permanent hydrographic connection between western and eastern Thessaly.